Islamist Terrorist Activity in 2000-2020: A Scoring Methodology - Olga S. Chikrizova (Vestnik RUDN. International Relations)
The relevance of the study of Islamist terrorism is due to its destructive impact on national and global security, as well as on the dialogue between Western and Eastern, particularly Muslim, nations since the early 2000s. Islamist terrorism reinforces entrenched prejudices against Islam and Muslims, leading to their demonization and the subsequent prevention of constructive interaction between communities professing different religions, thus hindering the establishment of relations based on mutual trust. This study examines the number of terrorist attacks committed by Islamist groups and their victims between 2000 and 2020, and tests the methodology for scoring their terrorist activities. Based on the Global Terrorism Database and the author’s sample of 155 groups broadcasting Islamist ideology, three stages of the development of Islamist terrorism were identified, a direct proportional relationship between the number of terrorist attacks and the number of victims was proven, and the geography of Islamist terrorist activity was analyzed. Methodologically, this study combines the analysis of terrorism as both a political phenomenon and a religious manifestation, and Islamist terrorist groups themselves are seen as political projects masquerading as religiously motivated communities. In contrast to the destabilization of Iraq, which along with Afghanistan became another platform for training terrorists, the terrorist attacks on September 11, 2001, had little impact on Islamist terrorism. Quantitative analysis revealed that the Middle East and North Africa was mistakenly perceived as the “epicenter” of Islamist terrorism in 2000-2020, as Southeast Asia was the leader in terrorist attacks in 2000, while South Asia occupied 1st place in 2003, 2005-2013, and 2018-2020. It has been confirmed that instability at the local and national levels serves as a fertile ground for Islamist terrorism. The possibilities and limitations of the proposed methodology are outlined, and the prospects for its further application in scientific studies of Islamist terrorism are described.